Characterization of Key Phytoconstituents in Nigella Oil from Diverse Sources and Their Transfer Efficiency During Oil Processing - Parbat Raj Thani; Joel B. Johnson; Surya Bhattarai; Tieneke Trotter; Kerry Walsh; Daniel Broszczak; Mani Naiker (Crops)
Nigella sativa L., which is commonly referred to as black cumin, is a globally recognized plant for the nutraceutical and pharmaceutical values of its seed oil. While numerous studies have investigated Nigella oil, there is a scarcity of information regarding the variation of key phytoconstituents in Nigella oil from diverse seed sources. It is also unclear whether the variation in phytoconstituents across different seed sources translates to variations in their respective oils, which is important for understanding their health benefits. Additionally, there is a gap in information on how specific phytochemicals transfer from seed to oil during the oil pressing. Therefore, this study investigated Nigella sourced from different genotypes and agricultural practices (planting densities and sowing times) to determine total phenolic content (TPC), antioxidant capacity (FRAP and CUPRAC), thymoquinone (TQ), and fatty acid composition. The results showed significant variation of TPC (87.4–144.1 mg gallic acid equivalents (GAE)/100 g), FRAP (454.1–560.9 mg Trolox equivalents (TE)/100 g), CUPRAC (356.3–482.5 mg TE/100 g), TQ (1493.5–2268.4 mg TQ/100 g), saturated fatty acid (SFA) (65.9–83.7 mg/g), monounsaturated fatty acid (MUFA) (42.5–67.8 mg/g), and polyunsaturated fatty acid (PUFA) (266.1–383.4 mg/g) in the oil derived from the seeds of different genotypes and agricultural practices. The total transfer of TPC, FRAP, and CUPRAC into the screw-pressed oil was relatively low, contributing only 2.3–3.7%, 7.1–11.7%, and 1.5–2.3%, respectively, of their total value in the respective seed. However, the transfer of TQ, SFA, MUFA, and PUFA was observed to be comparatively higher, contributing 32.8–48.5%, 60.8–84.2%, 45.6–74.4%, and 43.1–69.4%, respectively, of their total value in the respective seed. There was no strong correlation observed among TPC, FRAP, CUPRAC, and TQ, and none of the fatty acids showed a strong correlation with these variables.